HAUTEAS IS THE LIVING TREE OF THE DAWANESE PEOPLE - Mikhael Valens Boy (Program Studi Filsafat Agama Universitas Katolik Widya Mandira Kupang, 2020)
Before the arrival and the dominion of the Portuguese and the Dutchmen with its Christianity in the island of Timor, the Dawanese people of Timor have been inheriting and practising its own tribal religion. Even today this native religion has quite strongly and deeply influenced the religious conduct and behaviour of many Dawanese Catholics. These Catholics, beside practising their Catholic faith, they are still practising the “faith and the rite” of Hauteas. Hauteas itself is a strong big stick of wood with three branches, and sorrounding its foot there is a constructed circular altar of stones, that is Faot Makana. Hauteas is always built in the front of the sacred house of the Dawanese that is Uem Leu or Uem Adat. For the Dawanese people, the Hauteas is essentially “the living tree” since it is symbolizing, representing and manifesting the faith and belief of the Dawanese people to their gods. Hauteas functions also as an altar to pray and to offer the sacrifices. Hauteas is the “fountain of life”. The “life” of the Dawanese people comes through the trunk of this wood with its three branches. The longer and tallest branch of Hauteas symbolizes and represents the presence of the supreme god (Uis Neno), that is the lord of heaven. One of the lower and shorter branches symbolizes and represents the presence of Uis Pah, that is the lord of earth, and another one symbolizes and represents the presence of Be’i-Nai, that is the genealogical ancestors. The altar of stones (Faot Ben Makana) is “the offering and meeting place” between the Dawanese with their gods. The Dawanese people of Timor have a kind of “triune god” that gives and grants upon them life, safety, fertility, welfare, peace and blessings.